Foundations of national identity : from Catalonia to Europe - Llobera, Josep R. (New York ; Oxford : Berghahn Books, 2004)
"Since its emergence in the 19th century in response to feudalism, nationalism has been a mixed blessing. Originally seen as a positive force, often enough it has resulted in warfare and persecution of minorities, so much so that, over time, it has been considered a social evil whose apparent decline has been greeted as a positive development. The author disputes this or rather, he maintains that the picture that emerges is more complex: nationalism is not disappearing but has taken on a different form.
What we are experiencing is an increasing autonomy of ethnonations, i.e. nations without a state, in the wake of a weakening of the multinational states and the transfer of their sovereignty upwards, in the case of Europe to the federation of the European Union, and downwards to the "ethnonations"."--Jacket
1. The building-blocks of nationhood -- 2. National sentiments as an ultimate reality : a comparison between Catalonia and Poland -- 3. What's in a name? : kinship, territory and religion in the making of national identity -- 4. National character : myth and reality -- 5. God giveth them glory, for they speaketh the native tongue -- 6. The stuff that culture is made of -- 7. Distant splendours, latter-day miseries : the role of historical memory -- 8. Does nationalism inevitably lead to conflict and violence? -- 9. The future of nations in a United Europe -- 10. Explaining national identity : a theoretical closure.
Includes bibliographical references (pages 193-204) and index.
Print version record.
JSTOR
Keywords: Nationalism; Nationalism -- Spain -- Catalonia -- History; Nationalism -- Europe -- History; Nationalisme; Nationalisme -- Espagne -- Catalogne -- Histoire; Nationalisme -- Europe -- Histoire; nationalism; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; SOCIAL SCIENCE / Anthropology / Cultural; Nationalism; Europe; Spain -- Catalonia; Nationalisme; Nationale identiteit; History